Improvement of osseointegration by recruiting stem cells to titanium implants fabricated with 3D printing. Issue 1 (11th October 2019) - Bollman, Mary; Malbrue, Raphael; Li, Chunhong; Yao, Hong; Guo, Shengmin; Yao, Shaomian
Abstract: Slow and incomplete osseointegration and loss of osseointegration are major problems in dental and bone implants. We designed implants with interconnected 3D‐tubulous structures and hypothesized that such interconnecting 3D (I3D) structures would serve as a repository for chemoattractants to recruit stem cells to promote osseointegration. A concept Laser Mlab‐cusing‐R laser‐powder‐bed‐fusion (LPBF) 3D printing system was used to produce titanium implants with designed features. The implants were loaded (coated) with stromal cell–derived factor‐1 alpha (SDF‐1α), and subjected to stem cell recruitment. Implants were then surgically transplanted into the rabbit skull bone. After 12 weeks, osseointegration was analyzed by reverse‐torque test and the implants were examined for calcium deposition by Alizarin Red staining. The I3D implants attracted significantly more stem cells than solid implants when coated (loaded) with SDF‐1α. Greater torque force was needed to extract the I3D implants with 200 and 300 µm I3D structures than to extract solid implants from the skull. Generally, more calcium deposition was observed on the I3D implants than on the solid counterparts. LPBF 3D printing can be used to fabricate implants with complex structures. I3D‐tubulous structures of implants can retain chemoattractant for recruitment of stem cells to enhance osseointegration. Abstract : We fabricated metallic (titanium) implants with I3D designs using LPBF‐based 3D printing and conducted in vitro and in vivo experiments to test their stem cell recruitment capability and osseointegration characteristics. Our long‐term goal is to fabricate patient‐specific implants capable of rapid formation and maintenance of strong osseointegration using 3D printing to integrate stem cell recruitment techniques.